Novas tecnologias na cirurgia do buraco macular - Amaral, Oswaldo Ferreira Moura Brasil Do [UNIFESP] (2020)
Objective: To study new technologies in macular hole surgery, both in the feasibility of new techniques and in their anatomical and functional results. Methods: Three retrospective studies were performed. In the first study, 43 cases were revised where phacovitrectomy assisted by femtosecond laser was used to treat cataracts associated with various retinal pathologies, including macular holes. In the second study, we revised 46 eyes with macular holes submitted to 23g-caliber vitrectomy with internal limiting membrane peeling stained with brilliant blue G, with 3 years of follow-up. Only pseudophakic patients or those who underwent phacovitrectomy were included. In the third study, we revised the postoperative optical coherence tomography angiography of 10 cases of macular hole submitted to 2 different surgical techniques. Images of the outer retina were analyzed by ImageJ (imageJ.nih.gov) that created black-and-white pixel binarization histograms. Results: Femtosecond laser phacovitrectomy led to improved visual acuity in all cases. Mean visual acuity was 1.03 ±0.54 LogMAR in the baseline and 0.34 ±0.26 LogMAR in the final follow-up visit. There were no complications related to capsulorhexis, intraocular lens implantation, or scleral indentation. In this first study, perioperative retinal tears were detected in 11.6% of the cases, and there was no increase in postoperative central retinal thickness. In the second study, 42 (91.3%) eyes had macular hole closure after a single surgical procedure and 45 (97.8%) after one additional surgery. No complications related to the dye or reopening of the macular hole were observed. In the third study, a significantly higher percentage of white pixels was observed in the central 0.5mm of the internal limiting membrane removal group compared with the inverted or fragmented membrane group (12.3% x 5.6%, P=0.028). A significant correlation was found between visual acuity and the percentage of white pixels in the membrane removal group (r=0.917, P=0.029) when the square area of 3 x 3mm was evaluated. Conclusion: Phacovitrectomy assisted by femtosecond laser can successfully treat retinal diseases. Macular hole surgery with internal limiting membrane peeling stained by brilliant blue G leads to satisfactory anatomical and functional results. Analysis of the outer retinal layer by binarization histograms may be a new method for functional evaluation during macular hole healing, where the greatest number of white pixels would correspond to the highest cell viability.